A regeneration method of a retired lithium iron phosphate material and regenerated lithium iron phosphate
Patent Information
- Application Number
- CN202611020419.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-27
AI Technical Summary
然而,现有回收工艺在将黑粉重新制备为电池级磷酸铁锂材料时,普遍存在黑粉废料中残留大量炭和PVDF去除不完全,进入最终再生黑粉中,导致再生黑粉加工性能受损;同时再生黑粉倾向于保持原始黑粉废料的一次颗粒尺寸特征,导致其压实密度和电化学容量性能不佳
本申请第一方面采用粒径级配与喷雾造粒相结合的工艺路线:将补充锂铁等元素后的磷酸铁锂废料分别研磨至不同粒径区间,通过颗粒级配优化实现紧密堆积,提高再生磷酸铁锂材料的压实密度;对研磨后的材料进行喷雾造粒处理,该工艺改善了物料的流动特性,并在颗粒内部形成均匀孔隙结构,有利于空气烧结过程中残留碳源及粘结剂PVDF的充分氧化分解,从而提升再生材料的性能。
Smart Images

Figure CN122992207A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of battery material regeneration, specifically to a method for regenerating retired lithium iron phosphate materials and the regenerated lithium iron phosphate. Background Technology
[0002] A large number of lithium iron phosphate batteries are entering their retirement period. Their cathode black powder contains valuable elements such as lithium, iron, and phosphorus that can be recycled, and there is an urgent need for efficient recycling. However, existing recycling processes generally suffer from incomplete removal of residual carbon and PVDF in the black powder waste when reprocessing it into battery-grade lithium iron phosphate materials. These residual carbon and PVDF enter the final recycled black powder, resulting in impaired processing performance. At the same time, the recycled black powder tends to retain the primary particle size characteristics of the original black powder waste, leading to poor compaction density and electrochemical capacity performance. Summary of the Invention
[0003] The first aspect of this application provides a method for regenerating decommissioned lithium iron phosphate materials, comprising: A lithium source, an iron source, and a carbon source are added to the first lithium iron phosphate waste to obtain a first mixture. The first mixture is wet-milled to control the D50 particle size within the range of 400nm~600nm. It is then spray-dried to obtain a first powder. The first powder is sintered in an air atmosphere to obtain a first precursor. A lithium source, an iron source, and a second carbon source are added to the second lithium iron phosphate waste to obtain a second mixture. The second mixture is then wet-milled to control the D50 particle size within the range of 200nm to 300nm. After spray drying, a second powder is obtained. The second powder is then sintered in an air atmosphere to obtain a second precursor. The first precursor and the second precursor are mixed to obtain a mixed precursor. A third carbon source is added to the mixed precursor to obtain a mixed powder. The mixed powder is sintered in a non-oxidizing atmosphere. After sintering, airflow crushing is performed to obtain regenerated lithium iron phosphate.
[0004] In some optional embodiments of the first aspect of this application, the mass ratio of the first precursor and the second precursor in the mixed precursor is 1:(1~9).
[0005] In some optional embodiments of the first aspect of this application, the molar ratio of iron to phosphorus in the first mixture is (0.965~0.985):1, and the molar ratio of lithium to iron is (1.01~1.08):1; The amount of the first carbon source added is 5% to 10% of the mass of the first lithium iron phosphate waste.
[0006] In some optional embodiments of the first aspect of this application, the molar ratio of iron to phosphorus in the second mixture is (0.965~0.985):1, and the molar ratio of lithium to iron is (1.01~1.08):1; The amount of the second carbon source added is 5% to 10% of the mass of the second lithium iron phosphate waste.
[0007] In some optional embodiments of the first aspect of this application, the amount of the third carbon source added is 5% to 10% of the mass of the mixed precursor.
[0008] In some optional embodiments of the first aspect of this application, the grinding speed in the wet grinding of the first mixture is 1000 rpm to 2500 rpm; The first powder was sintered in air at a temperature of 400℃~800℃ for a duration of 120min~540min.
[0009] In some optional embodiments of the first aspect of this application, the grinding speed in the wet grinding of the second mixture is 1000 rpm to 2500 rpm; The second powder was sintered in air at a temperature of 400℃~800℃ for a duration of 120min~240min.
[0010] In some optional embodiments of the first aspect of this application, the mixed powder is sintered in a non-oxidizing atmosphere at a temperature of 700°C to 800°C for a duration of 180 min to 540 min.
[0011] In some optional embodiments of the first aspect of this application, the compaction density of the regenerated lithium iron phosphate is 2.45 g / cc to 2.54 g / cc.
[0012] The second aspect of this application provides a regenerated lithium iron phosphate, prepared by the above-described method for regenerating retired lithium iron phosphate materials.
[0013] Beneficial effects: The first aspect of this application adopts a process route combining particle size distribution and spray granulation: lithium iron phosphate waste after supplementation with elements such as lithium iron is ground into different particle size ranges, and the compaction density of the recycled lithium iron phosphate material is improved by optimizing the particle size distribution to achieve close packing; the ground material is then spray granulated. This process improves the flow characteristics of the material and forms a uniform pore structure inside the particles, which is conducive to the full oxidation and decomposition of residual carbon sources and binder PVDF during air sintering, thereby improving the performance of the recycled material. Attached Figure Description
[0014] Figure 1 This is an electron microscope image of the regenerated lithium iron phosphate prepared in Example 1 of this application; Figure 2 This is an electron microscope image of the regenerated lithium iron phosphate prepared in Comparative Example 2 of this application. Detailed Implementation
[0015] The present application will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the present application and are not intended to limit the present application.
[0016] In one embodiment, a method for regenerating decommissioned lithium iron phosphate materials is provided, comprising: A lithium source, an iron source, and a carbon source are added to the first lithium iron phosphate waste to obtain a first mixture. The first mixture is wet-milled to control the D50 particle size within the range of 400nm~600nm. It is then spray-dried to obtain a first powder. The first powder is sintered in an air atmosphere to obtain a first precursor. A lithium source, an iron source, and a second carbon source are added to the second lithium iron phosphate waste to obtain a second mixture. The second mixture is then wet-milled to control the D50 particle size within the range of 200nm to 300nm. After spray drying, a second powder is obtained. The second powder is then sintered in an air atmosphere to obtain a second precursor. The first precursor and the second precursor are mixed to obtain a mixed precursor. A third carbon source is added to the mixed precursor to obtain a mixed powder. The mixed powder is sintered in a non-oxidizing atmosphere. After sintering, airflow crushing is performed to obtain regenerated lithium iron phosphate.
[0017] In the above technical solution, the first and second lithium iron phosphate waste materials, which are supplemented with lithium, iron and carbon elements, are wet-milled to different particle size ranges, and then spray-dried separately. They are then sintered in an air atmosphere to remove a large amount of residual carbon and PVDF to obtain the first and second precursors. The first and second precursors are mixed and carbon elements are added. The mixture is then sintered in a non-oxidizing atmosphere. After sintering, airflow crushing is performed to obtain regenerated lithium iron phosphate.
[0018] In this embodiment, a process route combining particle size distribution and spray granulation is adopted: lithium iron phosphate waste that supplements lithium iron carbon is ground into different particle size ranges, and the compaction density of the recycled lithium iron phosphate material is improved by optimizing the particle size distribution to achieve close packing; the ground material is then spray granulated, which improves the flow characteristics of the material and forms a uniform pore structure inside the particles, which is conducive to the full oxidation and decomposition of residual carbon source and binder PVDF during air sintering, thereby improving the performance of the recycled material.
[0019] In this embodiment, both the first and second lithium iron phosphate waste materials originate from lithium iron phosphate batteries. The waste extraction process involves discharging the waste lithium iron phosphate batteries, separating the positive electrode material using physical methods such as mechanical crushing and sieving, and then processing it through chemical leaching and precipitation to obtain the lithium iron phosphate waste. In actual production, the first and second lithium iron phosphate waste materials can originate from the same batch of lithium iron phosphate batteries or from different batches.
[0020] In this embodiment, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; the iron source is selected from at least one of ferrous oxalate, ferric phosphate, ferrous sulfate, and ferric oxide; the first carbon source is selected from at least one of sucrose, glucose, and citric acid; the second carbon source is selected from at least one of sucrose, glucose, and citric acid; and the third carbon source is selected from at least one of sucrose, glucose, and citric acid.
[0021] In some optional embodiments of this application, the mass ratio of the first precursor and the second precursor in the mixed precursor is 1:(1~9). Specifically, the mass ratio of the first precursor and the second precursor in the mixed precursor can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or 1:9. It should be understood that other ratios within the above range are also applicable to the technical solutions of this embodiment.
[0022] In some optional embodiments of this application, the molar ratio of iron to phosphorus in the first mixture is (0.965~0.985):1, and the molar ratio of lithium to iron is (1.01~1.08):1; The amount of the first carbon source added is 5% to 10% of the mass of the first lithium iron phosphate waste.
[0023] In some optional embodiments of this application, the molar ratio of iron to phosphorus in the second mixture is (0.965~0.985):1, and the molar ratio of lithium to iron is (1.01~1.08):1; The amount of the second carbon source added is 5% to 10% of the mass of the second lithium iron phosphate waste.
[0024] In some optional embodiments of this application, the amount of the third carbon source added is 5% to 10% of the mass of the mixed precursor.
[0025] In some optional embodiments of this application, the grinding speed in the wet grinding of the first mixture is 1000 rpm to 2500 rpm; The first powder was sintered in air at a temperature of 400℃~800℃ for a duration of 120min~540min.
[0026] In some optional embodiments of this application, the grinding speed in the wet grinding of the second mixture is 1000 rpm to 2500 rpm; The second powder was sintered in air at a temperature of 400℃~800℃ for a duration of 120min~240min.
[0027] In some optional embodiments of this application, the mixed powder is sintered in a non-oxidizing atmosphere at a temperature of 700°C to 800°C for a duration of 180 min to 540 min.
[0028] In some optional embodiments of this application, the compaction density of the regenerated lithium iron phosphate is 2.45 g / cc to 2.54 g / cc.
[0029] The second aspect of this application provides a regenerated lithium iron phosphate, prepared by the above-described method for regenerating retired lithium iron phosphate materials.
[0030] The present application is further illustrated below with reference to embodiments and comparative examples. Unless otherwise specified, the raw materials, reagents, materials and equipment used in this application are all commercially available products conventionally used in the art.
[0031]
Example 1
[0032]
Example 2
[0033]
Example 3
[0034]
Example 4
[0035]
Example 5
[0036] Comparative Example 1 S1. Detect the elemental ratio of the first lithium iron phosphate waste, add lithium source and iron source to the first lithium iron phosphate waste, control the molar ratio of Fe to P, and the molar ratio of Li to Fe to satisfy: Fe:P=0.97:1, Li:Fe=1.03:1, and add 5% glucose by mass of the first lithium iron phosphate waste to obtain the first mixture. The first mixture was sintered at 500°C for 180 minutes in air atmosphere. After sintering, the first precursor was obtained. S2. Detect the elemental ratio of the second lithium iron phosphate waste, add lithium source and iron source to the second lithium iron phosphate waste, control the Fe to P molar ratio and the Li to Fe molar ratio to satisfy: Fe:P is 0.97:1, Li:Fe is 1.03:1, and add 5% glucose by mass of the second lithium iron phosphate waste to obtain the second mixture. The second mixture was sintered at 500°C for 180 min in air atmosphere. After sintering, the second precursor was obtained. S3. Mix the first precursor and the second precursor in a 1:1 mass ratio to obtain a mixed precursor. At the same time, add 10% glucose by mass of the mixed precursor to obtain a mixed powder. Sinter the mixed powder at 780℃ for 540 min under a nitrogen atmosphere. After sintering, perform airflow crushing to obtain regenerated lithium iron phosphate.
[0037] Comparative Example 2 S1. Detect the elemental ratio of the first lithium iron phosphate waste, add lithium source and iron source to the first lithium iron phosphate waste, control the molar ratio of Fe to P, and the molar ratio of Li to Fe to satisfy: Fe:P=0.97:1, Li:Fe=1.03:1, and add 5% glucose by mass of the first lithium iron phosphate waste to obtain the first mixture. Deionized water was added to the first mixture to obtain the first slurry, which had a solid content of 40%. The first slurry was then introduced into a sand mill for grinding. The speed of the sand mill was controlled at 2000 rpm, and the particle size of the grinding zirconium balls was 0.3 mm. The first slurry was ground in the sand mill to make the final D50 particle size 200 nm. The first slurry after grinding was then spray-dried using a spray dryer, with the inlet air temperature controlled at 220°C and the outlet air temperature at 110°C, to obtain the first powder. The first powder was then sintered at 500°C for 180 minutes in air atmosphere. After sintering, the first precursor was obtained. S2. Detect the elemental ratio of the second lithium iron phosphate waste, add lithium source and iron source to the second lithium iron phosphate waste, control the Fe to P molar ratio and the Li to Fe molar ratio to satisfy: Fe:P is 0.97:1, Li:Fe is 1.03:1, and add 5% glucose by mass of the second lithium iron phosphate waste to obtain the second mixture. Deionized water was added to the second mixture to obtain a second slurry with a solid content of 40%. The second slurry was then introduced into a sand mill for grinding. The speed of the sand mill was controlled at 2000 rpm, and the particle size of the grinding zirconium balls was 0.3 mm. The second slurry was ground in the sand mill to make the final D50 particle size 200 nm. The ground second slurry was then spray-dried using a spray dryer, with the inlet air temperature controlled at 220°C and the outlet air temperature at 110°C, to obtain the second powder. The second powder was then sintered at 500°C for 180 minutes in air atmosphere. After sintering, the second precursor was obtained. S3. Mix the first precursor and the second precursor in a 1:1 mass ratio to obtain a mixed precursor. At the same time, add 10% glucose by mass of the mixed precursor to obtain a mixed powder. Sinter the mixed powder at 780℃ for 540 min under a nitrogen atmosphere. After sintering, perform airflow crushing to obtain regenerated lithium iron phosphate.
[0038] Comparative Example 3 S1. Detect the elemental ratio of the first lithium iron phosphate waste, add lithium source and iron source to the first lithium iron phosphate waste, control the molar ratio of Fe to P, and the molar ratio of Li to Fe to satisfy: Fe:P=0.97:1, Li:Fe=1.03:1, and add 5% glucose by mass of the first lithium iron phosphate waste to obtain the first mixture. Deionized water was added to the first mixture to obtain the first slurry, which had a solid content of 40%. The first slurry was then introduced into a sand mill for grinding. The speed of the sand mill was controlled at 2000 rpm, and the particle size of the grinding zirconium balls was 0.3 mm. The first slurry was ground in the sand mill to make the final D50 particle size 400 nm. The first slurry after grinding was then dried by evaporation to obtain the first powder; the first powder was sintered at 500°C for 180 min in air atmosphere, and the first precursor was obtained after sintering was completed. S2. Detect the elemental ratio of the second lithium iron phosphate waste, add lithium source and iron source to the second lithium iron phosphate waste, control the Fe to P molar ratio and the Li to Fe molar ratio to satisfy: Fe:P is 0.97:1, Li:Fe is 1.03:1, and add 5% glucose by mass of the second lithium iron phosphate waste to obtain the second mixture. Deionized water was added to the second mixture to obtain a second slurry with a solid content of 40%. The second slurry was then introduced into a sand mill for grinding. The speed of the sand mill was controlled at 2000 rpm, and the particle size of the grinding zirconium balls was 0.3 mm. The second slurry was ground in the sand mill to make the final D50 particle size 200 nm. The second slurry after grinding was then dried by evaporation to obtain the second powder; the second powder was sintered at 500°C for 180 min in air atmosphere, and the second precursor was obtained after sintering was completed. S3. Mix the first precursor and the second precursor in a 1:1 mass ratio to obtain a mixed precursor. At the same time, add 10% glucose by mass of the mixed precursor to obtain a mixed powder. Sinter the mixed powder at 780℃ for 540 min under a nitrogen atmosphere. After sintering, perform airflow crushing to obtain regenerated lithium iron phosphate.
[0039] The conditions for each embodiment and comparative example are summarized in Table 1.
[0040] Table 1
[0041] [Performance Testing] The carbon content of the mixed precursors obtained in each embodiment and comparative example was tested, and the compaction density and 0.1C discharge specific capacity of the regenerated lithium iron phosphate obtained in each embodiment and comparative example were tested. The test results are shown in Table 2.
[0042] The testing methods for each parameter are as follows: (1) Particle size test: A laser particle size analyzer (such as Malvern 3000) was used to test the particle size distribution according to GB / T 19077-2016 / ISO13320:2009 "Laser diffraction method for particle size distribution". Before the test, the sample was dispersed in deionized water and ultrasonically dispersed for 20 min to avoid particle agglomeration.
[0043] (2) Carbon content test: The carbon content was determined using a high-frequency infrared carbon-sulfur analyzer. During the test, an appropriate amount of mixed precursor sample was accurately weighed and placed in a high-frequency induction furnace. The sample was fully combusted under oxygen-rich conditions. The generated carbon dioxide gas was detected by an infrared detector. The mass percentage of carbon in the sample was calculated based on the absorption peak intensity. Each group of samples was tested in parallel three times, and the average value was taken as the final result.
[0044] (3) Compacted density test: Accurately weigh 0.5000g of regenerated lithium iron phosphate powder, place it in a standard mold, and press it into shape under a pressure of 300MPa for 30s. After removing the pressed tablet, use a digital caliper to accurately measure the diameter and thickness of the tablet, calculate the volume according to the cylinder volume formula, and calculate the compacted density in combination with the sample mass. Each group of samples was tested 5 times, and the average value was taken after removing outliers.
[0045] (4) 0.1C discharge capacity test: Regenerated lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride (PVDF) were uniformly mixed at a mass ratio of 90:5:5, and a slurry was prepared using N-methylpyrrolidone (NMP) as a solvent. The slurry was uniformly coated onto an aluminum foil current collector and dried in a vacuum drying oven at 110℃ for 12 hours. The slurry was then pressed into a positive electrode sheet using a roller press. In an argon-protected glove box, CR2032 coin cells were assembled using a lithium metal sheet as the negative electrode and a 1 mol / L LiPF6 electrolyte (the solvent being a 1:1 volume mixture of ethylene carbonate and diethyl carbonate). After the batteries were allowed to stand for 12 hours to age, a charge-discharge test was conducted using a Blue Battery testing system at a constant temperature of 25±1℃. The voltage range was 2.0V~3.8V, and the charge-discharge rate was 0.1C (1C=170mA / g). The first discharge specific capacity was recorded. Three parallel batteries were tested for each sample, and the average value was taken as the final result.
[0046] Table 2
[0047] As shown in Table 2: The carbon content of the mixed precursors in Examples 1 to 5 was lower than that in Comparative Example 1, and the compaction density and 0.1C discharge specific capacity of the recycled lithium iron phosphate were higher than those in Comparative Example 1. This indicates that grinding and spray granulation can effectively improve the performance of recycled materials.
[0048] Compared with Comparative Example 2, the primary particles of Example 1 have obvious size gradation, while the primary particles of Comparative Example 2 are more uniform. Therefore, the compaction density of Example 1 is higher than that of Comparative Example 2, indicating that setting the corresponding particle size gradient ratio is beneficial to improving the compactness of the material.
[0049] Compared with Comparative Example 3, Example 1 uses spray granulation, while Comparative Example 3 does not. The carbon content of the mixed precursor in Example 1 is much lower than that in Comparative Example 3. The compaction density of the recycled lithium iron phosphate in Example 1 is higher than that in Comparative Example 3. This shows that spray granulation can promote the removal of carbon from the material and improve the compactness of the particles.
[0050] It should be noted that, in this document, "comprising," "including," or any other variation thereof is intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.
[0051] The various embodiments in this specification are described in a related manner. Similar or identical parts between embodiments can be referred to mutually. Each embodiment focuses on describing the differences from other embodiments. The above descriptions are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the principles of this application should be included within the scope of protection of this application.
Claims
1. A method for regenerating decommissioned lithium iron phosphate materials, characterized in that, include: A lithium source, an iron source, and a first carbon source are added to the first lithium iron phosphate waste to obtain a first mixture. The first mixture is wet-milled to control the D50 particle size within the range of 400nm to 600nm. It is then spray-dried to obtain a first powder. The first powder is sintered in an air atmosphere to obtain a first precursor. A lithium source, an iron source, and a second carbon source are added to the second lithium iron phosphate waste to obtain a second mixture. The second mixture is then wet-milled to control the D50 particle size within the range of 200nm to 300nm. After spray drying, a second powder is obtained. The second powder is then sintered in an air atmosphere to obtain a second precursor. The first precursor and the second precursor are mixed to obtain a mixed precursor. A third carbon source is added to the mixed precursor to obtain a mixed powder. The mixed powder is sintered in a non-oxidizing atmosphere. After sintering, it is subjected to airflow crushing to obtain regenerated lithium iron phosphate.
2. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The mass ratio of the first precursor to the second precursor in the hybrid precursor is 1:(1~9).
3. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The molar ratio of iron to phosphorus in the first mixture is (0.965~0.985):1, and the molar ratio of lithium to iron is (1.01~1.08):
1. The amount of the first carbon source added is 5% to 10% of the mass of the first lithium iron phosphate waste.
4. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The molar ratio of iron to phosphorus in the second mixture is (0.965~0.985):1, and the molar ratio of lithium to iron is (1.01~1.08):
1. The amount of the second carbon source added is 5% to 10% of the mass of the second lithium iron phosphate waste.
5. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The amount of the third carbon source added is 5% to 10% of the mass of the mixed precursor.
6. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The grinding speed during the wet grinding of the first mixture is 1000 rpm to 2500 rpm; The sintering temperature of the first powder in air atmosphere is 400℃~800℃, and the sintering time is 120min~540min.
7. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The grinding speed during the wet grinding of the second mixture is 1000 rpm to 2500 rpm; The second powder is sintered in air at a temperature of 400℃~800℃ for a duration of 120min~240min.
8. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The mixed powder is sintered in a non-oxidizing atmosphere at a temperature of 700℃~800℃ for a duration of 180min~540min.
9. The method for regenerating decommissioned lithium iron phosphate materials according to claim 1, characterized in that, The compaction density of the regenerated lithium iron phosphate is 2.45 g / cc to 2.54 g / cc.
10. A regenerated lithium iron phosphate, characterized in that, It is prepared by the regeneration method of retired lithium iron phosphate material according to any one of claims 1 to 9.